1998
DOI: 10.1111/j.1467-9906.1998.tb00415.x
|View full text |Cite
|
Sign up to set email alerts
|

The Community Development Industry System: A Case Study of Politics and Institutions in Cleveland, 1967–1997

Abstract: This article examines the emergence of community development corporations (CDCs) from a peripheral component of neighborhood-based community development in the late 1960s to a leading role in community development in the 1990s. An emphasis is placed on the historical development of CDCs as they have progressed from neighborhood social movements, to neighborhood-based organizations, to the current emergence of a citywide communio development industry system bringing CDCs together with traditional urban institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 8 publications
0
45
0
1
Order By: Relevance
“…In essence, Clavel and his associates argued for a restructuring of policy-making and implementation powers in order to promote greater accountability to constituents at the grassroots level. In the second piece of research, Yin (1998) examined the expansion of CDCs in Cleveland, Ohio, and argued that over time these organisations had become incorporated into local institutional networks. The crux of this argument was that CDCs had become part of a network of organisations that formed a community development industry system.…”
Section: Embedding Women-led Organisationsmentioning
confidence: 99%
“…In essence, Clavel and his associates argued for a restructuring of policy-making and implementation powers in order to promote greater accountability to constituents at the grassroots level. In the second piece of research, Yin (1998) examined the expansion of CDCs in Cleveland, Ohio, and argued that over time these organisations had become incorporated into local institutional networks. The crux of this argument was that CDCs had become part of a network of organisations that formed a community development industry system.…”
Section: Embedding Women-led Organisationsmentioning
confidence: 99%
“…A banker who criticized the initiative in his county as a ''waste of money'' put it this way, ' The white business elite's interest in community development is further suppressed by their general view of such programs as ''black initiatives'' targeting the black community. What is more, many alluded to Yin's (1998) concept of the ''community development industry system'' to describe such initiatives as merely Community Development 9 265 providing resources to organizations viewed as self-serving, ineffective, and corrupt. A white leader of a business association expressed this as follows, ''We've been through so many of these initiatives here.…”
Section: Racialized Institutions and Consensus-building Community Devmentioning
confidence: 99%
“…The community development industry system is now broader and more established; it has a history that enables it to be studied. In a rich case study, Yin (1998) showed how the "community development industry system" developed in Cleveland. CDCs progressed from largely independent, grassroots organizations, to a model of development built upon key relationships with government, philanthropy and churches.…”
Section: Maturation Of the Urban Community Development Fieldmentioning
confidence: 99%